Effect of pectin particles and cotton fibers on properties of thermoplastic cassava starch composites - Prachayawarakorn, Jutarat; Pattanasin, Worawan (My University, 2016)
Due to poor mechanical properties and high water uptake of thermoplastic starch (TPS), this research focused on property improvement of thermoplastic cassava starch (TPCS) using natural compatible polymers, i.e. pectin particles and cotton fibers. Different TPCS composites, reinforced by the pectin particles and/or the cotton fibers, were compounded and shaped using an internal mixer and a compression molding machine, respectively. It was found from infrared (IR) spectra that the peak position of O-H stretching of the TPCS polymer clearly shifted to lower wavenumber by the addition of the pectin particles and/or the cotton fibers. Moreover, the significant increase of stress at maximum load and Young’s modulus of the TPCS/pectin particle and the TPCS/cotton fiber composites was observed. The drop of water uptake was also found when the cotton fibers were incorporated into the TPCS matrix with/without pectin particles. In addition, X-Ray Diffraction, Scanning Electron Microscopy and Thermogravimetric Analysis were used to characterize different TPCS composites.
Keywords: Biodegradable polymer; Composite; Fibers; Pectin; Thermoplastic starch